Vidas submersas - o entre atos de olhares: Alejandro Jodorowsky e sua obra multimídia - Fabricio Trindade Pereira (2017)
This work is the reflective writing developed from the relations of the various aesthetic-political elements present in the images created by Alejandro Jodorowsky, in Melodrama Sacramental (1965), Santa Sangre (1989) and Las tres viejas (2003). Each artistic work, and its language specificities (theatrical event, audio visual / cinema and dramatic text), configure fictional realities that, in this work, are analyzed from concepts such as dialectical images (DIDI-HUBERMAN, 1998), sharing the sensitive (RANCIÈRE, 2005), emancipated spectator (RANCIÉRE, 2012), society of the spectacle (DEBORD, 1997) and will also use concepts of the Alejandro Jodorowsky. Keywords: images, Alejandro Jodorowsky, scenic actions, cinema, theater.